1999
DOI: 10.1583/1074-6218(1999)006<0011:lasfea>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Aneurysm Shrinkage Following Endovascular Aortic Aneurysm Repair: A Source of Intermediate and Late Complications

Abstract: In this study, longitudinal shrinkage of the sac following endovascular aortic aneurysm repair led to buckling or kinking of the endograft within 1 year in 69% of patients. This appears to be an important source of delayed complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(38 citation statements)
references
References 15 publications
1
36
0
1
Order By: Relevance
“…In addition, kinking may cause displacement of the iliac graft limb and subsequent secondary endoleak. Harris et al 7 reported a 69% incidence of buckling or kinking of endografts within 1 year. In our 2-year observation period, we saw moderate to severe changes in Ͼ50% of the Vanguard devices and observed a permanent change in stentgraft anatomy that continued to progress throughout follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, kinking may cause displacement of the iliac graft limb and subsequent secondary endoleak. Harris et al 7 reported a 69% incidence of buckling or kinking of endografts within 1 year. In our 2-year observation period, we saw moderate to severe changes in Ͼ50% of the Vanguard devices and observed a permanent change in stentgraft anatomy that continued to progress throughout follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, now that data from longer follow-up are becoming available, reports of secondary sequelae are appearing. [7][8][9] As one example, Harris et al 7 reported significant stent-graft kinking and buckling induced by longitudinal aneurysm shrinkage in almost 70% of their 26 cases after only 1 year.…”
mentioning
confidence: 99%
“…The first mechanism is the “accordion effect.” The shortening of the endovascular stent graft after release is followed by re-expansion of the stent itself to its natural length as a result the gradual distortion of the stent [8]. After EVAR, the vessel remodeling effect on the stent graft leads to kinking with an associated risk of endovascular stent graft occlusion [9]. Migration of the stent graft at the level of the proximal or distal fixation has also been reported as the cause of such geometric distortion.…”
Section: Discussionmentioning
confidence: 99%
“…Stauchungen des Stentgerüstes können erhebliche Faltenbildungen der Stentmembran verursachen. Entsprechende Befunde werden im Rahmen der klinischen Nachsorge mittels Radiographie erkannt [7,8,10,12,13]. Die damit verbundenen Fältelungen der Hüllmembran können den Blutfluss behindern und endoluminale Thrombusbildungen verursachen.…”
Section: Introductionunclassified